2020
DOI: 10.1029/2020gl090334
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Mantle Rocks Around the Lunar Imbrium Basin

Abstract: Basin-forming impacts expose material from deep within the interior of the Moon. Given the number of lunar basins, one would expect to find samples of the lunar mantle among those returned by the Apollo or Luna missions or within the lunar meteorite collection. However, only a few candidate mantle samples have been identified. Some remotely detected locations have been postulated to contain mantle-derived material, but none are mineralogically consistent upon study with multiple techniques. To locate potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…In any case, it is difficult to determine how the co‐existence and isolated olivine‐rich sites are formed on the lunar surface using only remote‐sensing data. Sample return missions and in‐situ analysis might provide important information for this issue (e.g., Bretzfelder et al., 2020; Li et al., 2019; Tartèse et al., 2019). In this case, the compositional information of bulk rocks, the Mg number of olivine, the mineral phases coexisting with olivine on a microscale and their textures, and the crystallization age may be important.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, it is difficult to determine how the co‐existence and isolated olivine‐rich sites are formed on the lunar surface using only remote‐sensing data. Sample return missions and in‐situ analysis might provide important information for this issue (e.g., Bretzfelder et al., 2020; Li et al., 2019; Tartèse et al., 2019). In this case, the compositional information of bulk rocks, the Mg number of olivine, the mineral phases coexisting with olivine on a microscale and their textures, and the crystallization age may be important.…”
Section: Discussionmentioning
confidence: 99%
“…The role of exposure events has important implications for the interpretation of mineral abundance using remote sensing data. Bretzfelder et al (2020) have reported that many parts of the SI and MA do not possess mantle-derived rocks, as evidenced by their excessively high concentrations of plagioclase mixed with mafic minerals. Nevertheless, we note that their argument is based on an overview of large-scale images spanning tens of kilometers, not on a detailed description of areas where LCP-rich or olivine-rich rocks are exposed, such as the outcrops shown in the present work.…”
Section: Imbriummentioning
confidence: 99%
“…Bretzfelder et al. (2020) presented average spectral coverage of tens to hundreds of kilometers in the Imbrium basin; however, they did not include a detailed description of the distribution and geological context of each LCP‐rich outcrop.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Spudis [6] studied the geology and composition of important basin deposits, including the Orientale and Nectaris basins, and systematically summarized the geological characteristics of another 45 lunar impact basins. Thus far, studies of the lunar basins have mostly focused on the structure of individual basins or considered the compositional characteristics of the basins [10][11][12]. In our research, we conducted a comparative analysis of three lunar basins, Dirichlet-Jackson, Nectaris, and Orientale, which were formed at different moments of early lunar history.…”
Section: Introductionmentioning
confidence: 99%